2018
DOI: 10.1158/1535-7163.mct-17-0850
|View full text |Cite
|
Sign up to set email alerts
|

A miR-29b Byproduct Sequence Exhibits Potent Tumor-Suppressive Activities via Inhibition of NF-κB Signaling in KRAS-Mutant Colon Cancer Cells

Abstract: We previously demonstrated that miR-29b-3p is a hopeful miRNA-based therapy against colorectal cancer. In this study, we aimed to clarify a value of miR-29b-1-5p as a next-generation treatment, especially for -mutant colorectal cancer. RT-PCR assay showed that the expression of miR-29b-3p was high, and its partner strand, miR-29b-1-5p, level was only negligible in clinical colorectal cancer samples. Mimic-miR-29b-1-5p significantly inhibited proliferation of-mutant colorectal cancer cell lines DLD1 and SW480 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…Their study revealed that miR‐4869 inhibits tumor cell proliferation by directly targeting KRAS and AKT. Inoue et al also reported that miR‐29b‐1‐5p is a TS‐miRNA and a passenger strand of miR‐29b‐3p. Compared with miR‐29b‐3p, miR‐29b‐1‐5p was significantly downregulated in K‐RAS mutant colon cancer patients.…”
Section: Delivery System Of Mirnamentioning
confidence: 96%
See 2 more Smart Citations
“…Their study revealed that miR‐4869 inhibits tumor cell proliferation by directly targeting KRAS and AKT. Inoue et al also reported that miR‐29b‐1‐5p is a TS‐miRNA and a passenger strand of miR‐29b‐3p. Compared with miR‐29b‐3p, miR‐29b‐1‐5p was significantly downregulated in K‐RAS mutant colon cancer patients.…”
Section: Delivery System Of Mirnamentioning
confidence: 96%
“…To improve the transduction efficacy of oligonucleotides, Hossain et al developed the carbonate apatite‐based delivery system. Using this system, several groups succeeded in the efficient transduction of TS‐miRNA into colon cancer cells . Hiraki et al identified miR‐4689 as a TS‐miRNA whose expression is downregulated by the K‐RAS mutant (KRAS G12V ).…”
Section: Delivery System Of Mirnamentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Inoue et al reported that mir-29b-3p can inhibit the activity of colon cancer cells mutated by KRAS by inhibiting NF-κB signaling pathway. 14 Wang et al demonstrated that mir-29b can inhibit the growth and metastasis of colorectal cancer by downregulating the expression of Tiam1 and inhibiting epithelial-mesenchymal transformation. 13 Wang et al 11 found that mir-29b can inhibit the proliferation of pancreatic cancer cells by targeting DNMT3b.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA expression profiles consist of determining different miRNA expression levels in multiple tumor samples (7). Previous studies have demonstrated that miRNA expression profiles are able to identify the tumor type, the staging and the other clinical characteristics, in addition to distinguishing between tumor and normal tissues, by which a variety of tumor and normal tissue samples may be analyzed systematically (8,9). The diagnostic accuracy rate of a tumor based on specific miRNA expression profiles is ≤70% (8).…”
Section: Introductionmentioning
confidence: 99%